THE ROLE OF FINANCIAL DIGITIZATION IN ENHANCING DIGITAL FINANCIAL INCLUSION IN IRAQ (REALITY AND CHALLENGES) - Malik Abdul Raheem Mohammed (Scholar Express Journals, 2025)
The research examines the impact of financial digitization and information and communication technology on digital financial inclusion. The article focuses on three main areas, including the development of digital financial services and the enhancement of financial inclusion in Iraq, as well as the analysis of financial digitization indicators and financial inclusion in Iraq. The digital transformation and the revolution in information and communication technology have led to the development of financial services by enhancing access for various segments of society and including them in financial services such as bank accounts and electronic payments through bank cards or digital wallets, among other financial services that have rapidly spread in recent years. This provides customers with increased diversity in products and services and a continuous reduction in costs due to the competition between traditional financial service providers and new non-traditional entrants. Additionally, it enables financial institutions to accelerate and enhance financial inclusion initiatives thanks to the ease of use, flexibility, cost-effectiveness, and security of mobile technology, all at a faster and lower cost. Financial digitization has enabled financial institutions to develop and deploy application-based banking services that encompass a more diverse customer base and new collaboration opportunities with both banking and non-banking companies
Keywords: Financial Inclusion; Financial Digitization; Financial Technology